2019
DOI: 10.1186/s12936-019-3045-y
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of combined screening methods for rapid detection of falsified and/or substandard medicines in the absence of a confirmatory method

Abstract: BackgroundThe influx of substandard and falsified medicines is a global public health challenge and its rapid detection is a key solution to the menace. This study used three screening methods and one confirmatory method for the quality assessment of 25 batches of artemether/lumefantrine dosage forms from the Ghanaian market to test that combined screening methods only can rapidly detect substandard and/or falsified medicines in areas where confirmatory methods may not be available.MethodsThe quality of arteme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Using a combination of these screening devices could also be an effective strategy. A recent study conducted in Ghana demonstrated the usefulness of combining three low cost (<USD $10,000) screening methods (GPHF-Minilab, colorimetry, and Counterfeit Drug Indicator) to quickly detect substandard and falsified artemether/lumefantrine products [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using a combination of these screening devices could also be an effective strategy. A recent study conducted in Ghana demonstrated the usefulness of combining three low cost (<USD $10,000) screening methods (GPHF-Minilab, colorimetry, and Counterfeit Drug Indicator) to quickly detect substandard and falsified artemether/lumefantrine products [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the wide variety of ways that pharmaceutical products can fail quality standards, the combination of several techniques is highly recommended to detect substandard or falsified medicines and to obtain an accurate final answer [8,16,17]. Several authors have combined screening and confirmation methods for the detection of SF medicines [1,[18][19][20][21][22][23][24] and recently, others attempted to evaluate the practical use of different handheld screening tools on the field [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, convenient methods to detect SF medicines are still urgently required 9 13 . Ensuring the quality of pharmaceuticals in the supply chain requires studies to establish the prevalence of SFs, as well as the development of effective analytical systems to identify and characterize SFs, and effective implementation of regulatory systems 14 .…”
Section: Introductionmentioning
confidence: 99%